2012
DOI: 10.1080/09640568.2011.636556
|View full text |Cite
|
Sign up to set email alerts
|

Environmental regulation and wages in China

Abstract: In this study we examine the extent to which firms pass back the cost of pollution regulation to workers, in the form of lower wages, using a unique matched employer-employee dataset for Shanghai. The benefits and costs of pollution regulation in China are important topics to study as China comes under increasing pressure to move from a single-minded focus on energy-driven economic growth to a more balanced approach to economic growth. The benefits of such a shift, particularly in terms of health, are relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The research conclusions are as follows: (1) The establishment of low-carbon cities in China. Although it has promoted the demand of enterprises for green development, it has a significant inhibitory effect on the overall industrial structure upgrade; (2) The empirical results of the geographical division show that this policy has a small negative impact on the industrial structure of the eastern region. Both the central and western regions showed obvious inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research conclusions are as follows: (1) The establishment of low-carbon cities in China. Although it has promoted the demand of enterprises for green development, it has a significant inhibitory effect on the overall industrial structure upgrade; (2) The empirical results of the geographical division show that this policy has a small negative impact on the industrial structure of the eastern region. Both the central and western regions showed obvious inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…First, strict environmental regulations have pushed up the prices of pollution-intensive production factors, greatly increasing the cost of pollution-intensive small and medium-sized enterprises, and even forced them to suspend production or transfer, thereby driving the redistribution of production factors and gradually shrinking the share of pollution-intensive industries to realize the effective adjustment of the industrial structure [1]. Second, high-standard environmental measures may promote the development of environmental protection services and related service industries for polluting companies [2], thereby enriching the region's industrial system characterized by low carbon emissions and improving the region Single industrial structure. Third, with the promotion of energy conservation, emission reduction and cleaner production concepts, the environmental protection and green awareness of the whole society will generally increase [3], and low-carbon and green lifestyles and consumption patterns are actively promoted, and then Green services and related industries for residents have also emerged.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, environmental regulation has increased the number of jobs. Mishra and Smyth [45] argued that when environmental regulation acts on industries with high labor demand, such as the environmental protection industry and related service industry, it will increase labor demand and improve employment level. Gray et al [46] utilized the DID method to evaluate the employment effect of the U.S. EPA regulations in the pulp and paper industry, and found that this policy does not significantly reduce employment, but may slightly increase employment.…”
Section: Environmental Regulation and Enterprise Employmentmentioning
confidence: 99%
“…However, the enhancement of environmental regulations can promote the development of new industrial sectors, such as environmental protection and cleaning departments, leading to an increase in the employment capacity (Bezdek et al, 2008;Mishra and Smyth, 2012). This will partly alleviate the unemployment brought about by the enhancement of environmental regulations.…”
Section: Introductionmentioning
confidence: 99%